ANALYSIS OF MACROECONOMIC DETERMINANTS INFLUENCING FOERIGN DIRECT INVESTMENT (FDI) IN INDONESIA IN THE PERIOD OF 1982-2012 - Hakim, M Zikril; Adi S, Putu Mahardika (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to investigate and to explain the relationship between macroeconomics determinants and foreign direct investments (FDI) in Indonesia. Data used in this study are secondary data in the form of time series of yearly data during the period of 1982-2012 which obtained from official website of World Bank.  It comprises FDI as dependent variables and Gross Domestic Product (GDP), Inflation, Exchange Rate and Openness in Indonesia as independent variables. This study also included Infrastructure in determining FDI inflows to Indonesia. Research methods employed in this study are: Ordinary Least Square (OLS) used to  analyze the long term relationship between dependent variable and independent variables and Error Correction Model (ECM) used to analyze the dynamic short term relationship between the dependent variable and independent variables and speed of adjustment of  model toward equilibrium. In addition, this study also employed classical assumption test to determine the validity of the model. The findings shows that GDP, infrastructure, inflation rate, exchange rate, and trade openness have significant influence in the long term to FDI inflows in Indonesia. GDP, infrastructure and trade openness have positive significant influence to FDI while inflation and exchange rate have negative significant influence to FDI. Meanwhile, the short term analysis shows that inflation has negative significant influence while trade GDP, openness and exchange rate have positive significant influence toward FDI inflows in Indonesia. The ECT value also shows negative significant 0.66, it means that the speed of adjustment of the model from disequilibrium is amounted for 66%. Based on the result of the study, it is recommends policymakers such as government, Bank  Indonesia and  Otoritas Jasa Keuangan (OJK)  to ensure the stability of macroeconomic determinants such as GDP, Exchange Rate, Inflation, and Trade Openness. Government should also improve its expenditure on the key consideration of infrastructure such as telephone lines, as a ways to accelerate the  improvement of FDI inflows. And to attract foreign investors, the government's incentive policy should also focus on the improvement of export performance. The policies that can be taken are in the form of reduced tax rate in the industrial sector, simplifying export procedures and production empowerment by increasing production of export and product promotion through exhibitions or websites, business partnership programs and export marketing management training.Keywords: FDI, GDP, Inflation, Exchange Rate, Openness, Infrastructure, ECM.